Karakteristik Kimia dan Organoleptik Cookies Tersubstitusi Tepung Labu Kuning - Maulidya B, Zhadilah Nur; Augustyn, Gelora H; Palijama, Syane (Universitas Pattimura, 2023)
Cookies are a form of instant food preparation made from a mixture of the main ingredients of wheat with the addition of sugar, butter, and others. There is a need for local food ingredients that can replace some wheat flour to add the nutritional content of cookies, especially vitamin A, and reduce the use of wheat flour by substituting pumpkin flour in making cookies. This study aims to determine the best agent of pumpkin flour substitution on cookies' chemical and organoleptic characteristics. This study used a completely randomized design with a single factor: pumpkin flour substitution with 4 treatment levels 0%, 20%, 40%, and 60%. The results showed that cookies with 20% pumpkin flour substitution treatment were the best treatment based on chemical characteristics, including moisture content 6.34%, ash content 2.22%, fat content 22.52%, protein content 9.57%, carbohydrate content 59.32% and 0.79% crude fiber content, as well as organoleptic characteristics both hedonic and hedonic quality include color 3.0 (like) and 3.12 (yellow), taste 3.00 (like) and 2, 33 (slightly pumpkin flavoured), texture 3.00 (like) and 2.33 (a bit crunchy), and overall 3.00 (like).